1997
DOI: 10.1103/physrevlett.79.4381
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Surfactant Driven Instability in a Hele-Shaw Cell

Abstract: A surfactant driven instability is observed in the air-liquid interface of an aqueous surfactant solution moving inside a prewetted glass Hele-Shaw cell with a gap width of 300 mm when the viscous surfactant solution is pushing on the less viscous air. This is the reverse direction of the wellknown Saffman-Taylor instability. The fluctuations produced by the instability will develop into a steady state cellular pattern with the sharp fingers pointing in the opposite direction of the motion of the interface. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
1
23
4
Order By: Relevance
“…This instability relies on the integration of partially wettable particles to the meniscus driven by the minimization of interfacial energy. A reverse Saffman-Taylor instability in the presence of surfactants has been previously reported in the literature by Chan et al [11] and then by Fernandez et al [12], but, in contrast to these studies, the fingers observed in our studies with particles are not limited in depth.…”
contrasting
confidence: 56%
“…This instability relies on the integration of partially wettable particles to the meniscus driven by the minimization of interfacial energy. A reverse Saffman-Taylor instability in the presence of surfactants has been previously reported in the literature by Chan et al [11] and then by Fernandez et al [12], but, in contrast to these studies, the fingers observed in our studies with particles are not limited in depth.…”
contrasting
confidence: 56%
“…The development of the reversed viscous fingering instability has been investigated both theoretically and experimentally by considering the addition of surfactants to the moving interface, or to the Hele-Shaw cell plates [14][15][16][17][18][19][20]. The presence of the surfactant may cause the surface tension to vary along * jme@df.ufpe.br the fluid-fluid boundary, facilitating the occurrence of local disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…In the above example, like many others, surfactant-generated Marangoni effects just modify the existing solution to leading order, but do not introduce any new fundamental instabilities. The experiments conducted by Chan & Liang (1997), however, have demonstrated that surface-active substances crucially influence the Saffman-Taylor phenomenon and even reverse its stability characteristics. Figure 1 gives a diagram of the experiment: a Hele-Shaw cell is dipped into a surfactant solution at speed V .…”
Section: Introductionmentioning
confidence: 99%